2016
DOI: 10.1039/c5nj02307f
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear cyclooctatetraene–iron carbonyl complexes: examples of fluxionality and valence tautomerism

Abstract: Fluxionality and valence tautomerism are studied in the experimentally observedtrans-(η4,η4-C8H8)Fe2(CO)6,cis-(η3,η3-C8H8)Fe2(CO)6, andcis-C8H8Fe2(CO)4(μ-CO) structures using density functional theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…In this redox process, the Co­(III) ion is reduced to Co­(II) and the CAT ligand is oxidized to its semiquinonato (SQ) form. VT transitions involving SQ-CAT ligand are by far the most reported in the literature, mainly in Co, and Mn isolated complexes, but also in various d block elements such as Fe, Ni, Rh, and V. VT transitions were also observed in four unidimensional (1D) polymers and one Co-based bidimensional (2D) coordination polymer. , Other ligands than SQ-CAT are less common in VT systems, with a dozen examples reported so far, involving porphyrin derivatives, cyclopentadienyl, or bis­(diisopropyl-phenylimino)­acenaphthene. In the latter case, VT was reported for Yb …”
Section: Introductionmentioning
confidence: 99%
“…In this redox process, the Co­(III) ion is reduced to Co­(II) and the CAT ligand is oxidized to its semiquinonato (SQ) form. VT transitions involving SQ-CAT ligand are by far the most reported in the literature, mainly in Co, and Mn isolated complexes, but also in various d block elements such as Fe, Ni, Rh, and V. VT transitions were also observed in four unidimensional (1D) polymers and one Co-based bidimensional (2D) coordination polymer. , Other ligands than SQ-CAT are less common in VT systems, with a dozen examples reported so far, involving porphyrin derivatives, cyclopentadienyl, or bis­(diisopropyl-phenylimino)­acenaphthene. In the latter case, VT was reported for Yb …”
Section: Introductionmentioning
confidence: 99%
“…However, Gusev recently 11 demonstrated that the newer M06-L functional is a good-quality and relatively fast local density functional for computational work in organometallic chemistry and catalysis. The M06-L functional has been tested in our recent work, 10,12 which gives satisfactory performance in both speed and accuracy. For this reason, the M06-L method 13 as well as the previously used B3LYP 14,15 and BP86 16,17 methods were used in this work.…”
Section: Theoretical Methodsmentioning
confidence: 99%